If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x(-6x + -5 + 2a) = 0 Reorder the terms: -7x(-5 + 2a + -6x) = 0 (-5 * -7x + 2a * -7x + -6x * -7x) = 0 Reorder the terms: (-14ax + 35x + 42x2) = 0 (-14ax + 35x + 42x2) = 0 Solving -14ax + 35x + 42x2 = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-35x' to each side of the equation. -14ax + 35x + -35x + 42x2 = 0 + -35x Combine like terms: 35x + -35x = 0 -14ax + 0 + 42x2 = 0 + -35x -14ax + 42x2 = 0 + -35x Remove the zero: -14ax + 42x2 = -35x Add '-42x2' to each side of the equation. -14ax + 42x2 + -42x2 = -35x + -42x2 Combine like terms: 42x2 + -42x2 = 0 -14ax + 0 = -35x + -42x2 -14ax = -35x + -42x2 Divide each side by '-14x'. a = 2.5 + 3x Simplifying a = 2.5 + 3x
| 7t=150.5 | | 2-5/6x=1/3x-12 | | 24y+7=2 | | 12y*-20y-25= | | (z^2)-(3-2i)z+(1-3i)=0 | | 12y*2-20y-25= | | 2x^2+5=5 | | 3/8x-2=1/4x+3 | | X^8+5x^4-6=0 | | 3n=10 | | 5+5sqrt(x+5)=21 | | 5+5sqrtx+5=21 | | 4x^2+23x-2=0 | | -8+4(x-2)+4(x-1)-3x=0 | | 121x^3-4x=0 | | 2x-8y-7x+4y= | | -1+2x=-4+35x | | 15x+14=-94-7x | | 25-6x=7-8x | | f(x)=x^7+6x^6+5x^5 | | 10=-34-1x | | -5=9x-95 | | 40=7x-16 | | -3/8*-5/-7*2= | | 8x-16=6-3x | | c=15.7 | | 4x-120=2x+60 | | 6+30x=15x+12 | | (2k-3)x^2+2(k-3)x+1=0 | | 8K+ar=r-5y | | 2x+7=-21-2x | | x-4=4x-13 |